2020
DOI: 10.1101/2020.06.07.138461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-lasting event-related beta synchronizations of electroencephalographic activity in response to support-surface perturbations during upright stance

Abstract: word count: 299 words Abstract Movement related beta band cortical oscillations, including post-movement beta rebound and desynchronization/synchronization observed during Go/NoGo tasks, have drawn attention in motor control literature, particularly during movements of upper extremities. However, fewer study focused on beta band oscillations during postural control in upright stance. Here, we examined beta rebound and other components of electroencephalogram (EEG) activity during perturbed upright stance to in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 82 publications
0
4
2
Order By: Relevance
“…We observed greater modulation of sensorimotor beta oscillations evoked by larger, more challenging balance perturbations, and in individuals with lower balance ability. In contrast to prior studies that have observed beta power modulation beginning prior to the onset of unpredictable balance perturbations [ 35 , 36 , 37 , 38 , 39 , 40 ], we found modulation of beta power occurred ~50 ms after the onset of perturbations. Further, the time course of evoked beta power was similar to that of evoked balance-correcting muscle activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We observed greater modulation of sensorimotor beta oscillations evoked by larger, more challenging balance perturbations, and in individuals with lower balance ability. In contrast to prior studies that have observed beta power modulation beginning prior to the onset of unpredictable balance perturbations [ 35 , 36 , 37 , 38 , 39 , 40 ], we found modulation of beta power occurred ~50 ms after the onset of perturbations. Further, the time course of evoked beta power was similar to that of evoked balance-correcting muscle activity.…”
Section: Discussioncontrasting
confidence: 99%
“…While beta oscillations have been linked to sensorimotor information processing and motor control, beta oscillatory activity in the context of balance-correcting behavior and associations with balance ability are poorly understood. Previous studies have consistently demonstrated that cortical beta activity over central midline scalp regions is modulated during standing balance recovery [ 35 , 36 , 37 , 38 , 39 , 40 ], though there is some discrepancy regarding the directionality of change that may originate from differences in the perturbation and analysis methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…We observed greater modulation of sensorimotor beta oscillations evoked by larger, more challenging balance perturbations, and in individuals with lower balance ability. In contrast to prior studies that have observed beta power modulation beginning prior to the onset of unpredictable balance perturbations (Nakamura et al, 2020;Peterson & Ferris, 2018Solis-Escalante et al, 2019;Varghese et al, 2014Varghese et al, , 2019, we found modulation of beta power occurred ~50 ms after the onset of perturbations. Further the time course of evoked beta power was similar to that of evoked balance-correcting muscle activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the transient N1 potential that reflects more general neural features of attention (C. E. Little & Woollacott, 2015;Quant et al, 2004) or threat perception (Adkin et al, 2008;Mochizuki et al, 2010), cortical beta power has greater potential for involvement in balance-correcting behavior because it remains elevated throughout balance recovery with a time course comparable to the balance-correcting motor response. Prior studies have shown beta power modulation beginning prior to the onset of unpredictable balance perturbations (Nakamura et al, 2020;Peterson & Ferris, 2018Solis-Escalante et al, 2019;Varghese et al, 2014Varghese et al, , 2019, making it unclear whether the modulation was occurring in anticipation of, rather than in response to, the balance perturbations. The apparent modulation of beta power prior to perturbation onset in these cases may have resulted from the loss of temporal resolution that occurs with the use of larger sliding time windows that are necessary for the inclusion of lower oscillatory frequencies (e.g.…”
Section: Increased Cortical Recruitment With Increasing Balance Diffimentioning
confidence: 99%
See 1 more Smart Citation